Necrotizing soft tissue infection: principles of diagnosis and management. Issue 3 (June 2016) - Harrison, William D.; Kapoor, Birender
Abstract: Necrotizing soft tissue infection (NSTI) is a rare and sometimes deadly infective condition affecting the subcutaneous tissue and fascia, with or without involvement of the muscle. This paper reviews the broader definition of necrotizing infections, including infective myositis. The symptoms, signs and laboratory-based diagnostic tools are discussed. Early diagnosis of NSTI is often a challenge due to inconsistent features of necrosis at presentation; however, features of necrosis can also develop within hours. Clear risk factors and patterns of bacteriology exist, some of which define prognosis. Modern concepts, including debridement zones and an operative strategy are discussed. Time to debridement significantly impacts mortality outcomes and is a key message of this article.